The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/cen.12966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute and chronic glucocorticoid therapy on insulin sensitivity and postprandial vascular function

Abstract: Prednisolone-induced insulin resistance is not associated with postprandial vascular dysfunction in patients with rheumatoid arthritis. Reduced sympathetic activity may contribute to the reduction in postprandial arterial stiffness with acute prednisolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
(62 reference statements)
1
23
0
Order By: Relevance
“…With regard to the effect of GC therapy, certain studies reported a positive effect or the lack of effect on endothelial function in RA patients [14][15][16][17][18]. These discrepant results may be explained by the great heterogeneity in RA disease stage, dosages and treatment duration of GCs, or therapies Glucocorticoids and endothelial function in arthritis V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 188: 208-218 associated with GCs among these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the effect of GC therapy, certain studies reported a positive effect or the lack of effect on endothelial function in RA patients [14][15][16][17][18]. These discrepant results may be explained by the great heterogeneity in RA disease stage, dosages and treatment duration of GCs, or therapies Glucocorticoids and endothelial function in arthritis V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 188: 208-218 associated with GCs among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a significant evolution in the treatment of RA, the majority of patients still use GCs alone or in combination with diseasemodifying anti-rheumatic drugs (DMARDs). Regarding the endothelial function specifically, only five studies in RA investigated the effects of GCs on ED, and reported that GCs had no deleterious effect [14][15][16][17] or even beneficial effects on vascular function [18]. GCs might increase CV risk (CVR) by increasing CV risk factors (dyslipidaemia, hypertension, insulin resistance).…”
Section: Introductionmentioning
confidence: 99%
“…While most studies showed no deterioration of endothelial function after a treatment with a low dose or a bolus of GCs, one study reported improvement in endothelial function after 1 year of treatment with a low dose of a GC [48]. The effects of GCs are likely independent on disease duration [49]. Thus, despite the classical assumption that GCs are responsible for deterioration in endothelial function, no available data in the literature demonstrate such an effect in RA.…”
Section: Resultsmentioning
confidence: 99%
“…)Single doseCompared to baselineFMD3.3 % vs 3.1 % (NS)4Veselinovic et al [48]Serbia525.723.69 ± 0.84Prednisolone 7.5 mg/day (p.o.) + DMARDAt least 1 yearRA patients without GCFMD9.16 % ± 7.03 vs 12.6 % ± 5.49 P  = 0.0057Radhakutty et al [49]Australia18--Prednisolone 6 mg/day (p.o. )7 daysRA patients taking prednisolone for 6 months (4–10 mg/day)PATNo effect7

GC glucocorticoid, RA rheumatoid arthritis, DAS28 disease activity score in 28 joints, DMARD disease-modifying antirheumatic drug, i.v .

…”
Section: Effects Of Gc On Endothelial Function In Ramentioning
confidence: 99%
See 1 more Smart Citation